Protective effects of dexrazoxane against acute ischaemia/reperfusion injury of rat hearts - Neckář, Jan; Boudíková, Adéla; Mandíková, Petra; Stěrba, Martin; Popelová, Olga; Mikšík, Ivan; Dabrowská, Ludmila; Mráz, Jaroslav; Geršl, Vladimír; Kolář, František (Canadian journal of physiology and pharmacology, 2012)
Dexrazoxane (DEX), an inhibitor of topoisomerase II and intracellular iron chelator, is believed to reduce the formation of reactive oxygen species (ROS) and protects the heart from the toxicity of anthracycline antineoplastics. As ROS also play a role in the pathogenesis of cardiac ischaemia/reperfusion (I/R) injury, the aim was to find out whether DEX can improve cardiac ischaemic tolerance. DEX in a dose of 50, 150, or 450 mg·(kg body mass)(-1) was administered intravenously to rats 60 min before ischaemia. Myocardial infarct size and ventricular arrhythmias were assessed in anaesthetized open-chest animals subjected to 20 min coronary artery occlusion and 3 h reperfusion. Arrhythmias induced by I/R were also assessed in isolated perfused hearts. Only the highest dose of DEX significantly reduced infarct size from 53.9% ± 4.7% of the area at risk in controls to 37.5% ± 4.3% without affecting the myocardial markers of oxidative stress. On the other hand, the significant protective effect against reperfusion arrhythmias occurred only in perfused hearts with the dose of DEX of 150 mg·kg(-1), which also tended to limit the incidence of ischaemic arrhythmias. It is concluded that DEX in a narrow dose range can suppress arrhythmias in isolated hearts subjected to I/R, while a higher dose is needed to limit myocardial infarct size in open-chest rats.
Keywords: reaktivní formy kyslíku; techniky in vitro; Electrocardiography; modely nemocí na zvířatech; Dose-Response Relationship, Drug; Razoxane; reperfuzní poškození myokardu; krysa rodu Rattus; výsledek terapie; zvířata; infarkt myokardu; Myocardial Reperfusion Injury; Reactive Oxygen Species; potkani Wistar; Perfusion; kardiovaskulární látky; Rats, Wistar; Male; srdeční arytmie; perfuze; Myocardial Infarction; razoxan; Treatment Outcome; In Vitro Techniques; Rats; vztah mezi dávkou a účinkem léčiva; Arrhythmias, Cardiac; Animals; Cardiovascular Agents; mužské pohlaví; Acute Disease; Disease Models, Animal; akutní nemoc; elektrokardiografie